2008
DOI: 10.1063/1.2903903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dust size distribution on dust acoustic waves in two-dimensional unmagnetized dusty plasma

Abstract: For unmagnetized dusty plasma with many different dust grain species containing both hot isothermal electrons and ions, both the linear dispersion relation and the Kadomtsev–Petviashvili equation for small, but finite amplitude dust acoustic waves are obtained. The linear dispersion relation is investigated numerically. Furthermore, the variations of amplitude, width, and propagation velocity of the nonlinear solitary wave with an arbitrary dust size distribution function are studied as well. Moreover, both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…Figure 13 shows the quantum effects through the variation of H on the soliton width that shows W decreases as H increases. the estimated expressions ͑up to a 6 ͒ within the current study are more accurate and reasonable than the simple ones suggested by He et al 20 ͑they consider expansions up to a 3 only͒.…”
Section: B Polynomial Dsdmentioning
confidence: 61%
See 2 more Smart Citations
“…Figure 13 shows the quantum effects through the variation of H on the soliton width that shows W decreases as H increases. the estimated expressions ͑up to a 6 ͒ within the current study are more accurate and reasonable than the simple ones suggested by He et al 20 ͑they consider expansions up to a 3 only͒.…”
Section: B Polynomial Dsdmentioning
confidence: 61%
“…12,17,18 Since, the Gaussian DSD is accepted in laboratory plasmas, 19 the polynomial DSD is the general form of the size distribution function in dusty plasmas. 12,20 It is remarked here that the DSD may be discrete or continuous, however, the continuous model is the most reasonable. 17,18 Moreover, in the last few years, a large focus has been carried out on QDIAWs and their related phenomena.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[7][8][9] While the Gaussian DSD is accepted in laboratory plasmas, 11 the polynomial DSD is the general form of the size distribution function in dusty plasmas. 12 In the past, plasma particles have been considered to behave classically, but in the last few years much attention has been focused on quantum effects in plasma systems. 13 When the de-Broglie wavelength of particles composing the plasma ͑which is the spatial extension of the wave function due to quantum uncertainty principal͒, B = ប / mV T , can be comparable with the dimensions of the system, quantum mechanical effects play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…12 The most widely applicable one is the power law distribution because of its various applications in space plasmas. [7][8][9] While the Gaussian DSD is accepted in laboratory plasmas, 11 the polynomial DSD is the general form of the size distribution function in dusty plasmas.…”
Section: Introductionmentioning
confidence: 99%